PENGARUH TERAPI BERMAIN TERHADAP TINDAKAN KOOPERATIF ANAK USIA 3-5 TAHUN DALAM MENJALANI PERAWATAN DI RUANGAN ANAK RUMAH SAKIT PELAMONIA MAKASSAR - Alia Andriany (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: The purpose of this study was to see the effect of play therapy on cooperative action of children aged 3-5 years in undergoing treatment in the child's room. Method: The research design used in this study is cross sectional that researchers do observation or variable measurement at one time . The sample size in this study are 30 respondents who match the inclusion criteria. The data were collected by using questionnaires. Results: The results showed that there was a coloring effect on cooperative action of children (p = 0,017), there was influence of talking to cooperative action of child (p = 0,014). And there is the effect of drawing on child cooperative action (p = 0,003). Conclusion: The conclusion in this study is that there is a relationship between coloring, speaking, and drawing on cooperative actions of children. Suggestions: Suggestions The results of this study are suggested for nursing education in order to be useful to increase the knowledge of students about the importance of understanding and applying the influence of play therapy on cooperative action in undergoing treatment